Measuring the quality of e-commerce websites using analytical hierarchy process - Umar Abdul Aziz; Arif Wibisono; Amna Shifia Nisafani (Universitas Ahmad Dahlan, 2019)
Improving website quality for e-commerce website is indispensable since it affects customer satisfaction. There are several aspects of website quality that should be considered. Unfortunately, what criteria that should be prioritized is still under research. This research aims to identify the priority of website quality criteria and incorporate these criteria to measure the quality of ten e-commerce websites in Indonesia using Analytical Hierarchical Process (AHP). This study interviews two experts to assign priority for each criterion. In the end, this study has found that availability is the uttermost aspect to consider. Furthermore, this study also found that OLX.com is the best Customer-to-Customer (C2C) e-commerce in Indonesia in terms of website quality. This research is useful for any e-commerce technical developer to improve his/her website in twofold: 1) criteria priority to improve the quality of C2C e-commerce websites and 2) website quality ranking of C2C e-commerce.